Regional variation in low-value musculoskeletal surgery: a nationwide study from the Finnish Care Register - Ponkilainen, Ville; Laurema, Anniina; Mattila, Ville M; Karjalainen, Teemu (Acta orthopaedica, 2024)
Background and purpose: Healthcare systems globally are grappling with resource constraints and rising costs. Concerns have been raised about “low-value” care, which consumes healthcare resources without benefiting patients. We aimed to examine regional differences in common low-value musculoskeletal surgeries in Finland and explore explanatory factors behind the variation.Methods: Using data from the Finnish Care Register for Health Care, surgeries conducted from 2006–2007 compared with 2020–2021 were analyzed across 20 hospital districts. Selected surgeries (acromioplasty, rotator cuff repair, partial meniscectomy, wrist arthroscopy, ankle arthroscopy, and distal radius fracture fixation) were categorized based on NOMESCO procedure codes, and incidence rates in older populations were calculated based on population size derived from Statistics Finland.Results: We found substantial regional disparities in low-value surgeries. The incidence rates were higher in hospitals with high historical incidence rates and smaller population sizes, suggesting that the uptake of evidence is slower in small non-academic hospitals.Conclusion: The incidence of low-value surgery is declining but regional differences remain large. It is unlikely that regional variation in disease incidence explains such large variation in low-value surgery. Instead, local treatment culture seems to be the driving force behind low-value surgery, and the practices seem to be more entrenched in small hospitals.